2014
DOI: 10.1108/scn-07-2013-0027
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric neuropsychological assessment: an analysis of parents’ perspectives

Abstract: Purpose -Modern healthcare services are commonly based on shared models of care, in which a strong emphasis is placed upon the views of those in receipt of services. The purpose of this paper is to examine the parents' experiences of their child's neuropsychological assessment. Design/methodology/approach -This was a mixed-methodology study employing both quantitative and qualitative measures. Findings -The questionnaire measure indicated a high overall level of satisfaction. Qualitative analysis of parental i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
2
4
0
Order By: Relevance
“…Results of several studies, especially qualitative comments from both parents and teachers, highlight the benefits of reports that are concise and have minimal jargon Cheung et al, 2014;Keenan et al, 2019;Postal et al, 2018;Stark et al, 2014). This observation is consistent with expert opinion about the disadvantages of lengthy, technical report-writing styles (Donders, 1999).…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…Results of several studies, especially qualitative comments from both parents and teachers, highlight the benefits of reports that are concise and have minimal jargon Cheung et al, 2014;Keenan et al, 2019;Postal et al, 2018;Stark et al, 2014). This observation is consistent with expert opinion about the disadvantages of lengthy, technical report-writing styles (Donders, 1999).…”
Section: Discussionsupporting
confidence: 71%
“…Compared to children who did not receive a neuropsychological evaluation, those who did had a greater increase in the rate of 1) child participation in special education services, 2) initiation of ADHD medication, and 3) parent management training Rate of participation in individual therapy also increased, but this was similar between the two groups -Quillen, 2011 Parents followed 48% of recommendations Only 60% of parents gave the report to the school, though this was recommended for all Adherence varied substantially by parent 97% of implemented recommendations were perceived as helpful -(continued) (25%). Interestingly, two studies which allowed for qualitative remarks from parents suggested mixed views on reports, with some parents describing reports positively, and others indicating that they were too long, overly technical, or confusing (Cheung et al, 2014;Stark et al, 2014). These findings support the utility of reports, but also indicate opportunities for improvement to ensure that reports are accessible to parents.…”
Section: Pritchard 2014mentioning
confidence: 93%
See 3 more Smart Citations